Stigmasterol, rengyolone, 2-phenylethyl β-D-glucopyranoside and n-tetradecyl-β-D-glucopyranoside from the flowers of Nyctanthes arbor-tristis Linn (Bangladesh Journal of Scientific and Industrial Research, 2019)
A phytochemical investigation was conducted on the flowers of Nyctanthesarbor-tristis Linn. For isolation of compounds, the dried flower’s powder was successively extracted with n-hexane, dichloromethane, ethyl acetate and methanol. The extracts were fractionated using different chromatographic techniques and four compounds were isolated. Stigmasterol (1) from n-hexane, rengyolone (2) from dichloromethane and two other compounds namely, 2-phenylethyl β-D-glucopyranoside (3) and n-tetradecyl-β-D-glucopyranoside (4) from ethyl acetate extract, were isolated. These compounds (1-4) were characterized on the basis of IR, 1H NMR, 13C NMR, DEPT-135 NMR. Compounds 1 and 3 were isolated for the first time from this plant while compound 4 has been isolated and completely characterized from this plant as well as from the natural sources.Bangladesh J. Sci. Ind. Res.54(3), 275-282, 2019